PENGARUH PEMBERIAN EDUKASI TERHADAP PENGETAHUAN IBU TENTANG TERAPI MUSIK UNTUK MENINGKATKAN KUALITAS TIDUR BAYI USIA 0-12 BULAN - Vina Syafira; Devy Lestari Nurul Aulia; Dyka Aidina (Universitas Batam, 2024)
This research investigates the effects of educational interventions on maternal understanding of music therapy's role in enhancing sleep quality for infants aged 0-12 months. The investigation was carried out at Posyandu Mawar No. 39 Telaga Indah, employing a quasi-experimental methodology with control and experimental cohorts. Information was gathered via questionnaires administered prior to and following the educational session. The primary objective was to evaluate the shift in mothers' knowledge before and after exposure to the educational program and to assess its efficacy. The findings revealed a notable enhancement in comprehension among mothers in the experimental group relative to the control group. This outcome suggests that targeted instructional interventions can effectively bolster mothers' grasp of music therapy and its potential benefits for improving infant sleep patterns. In light of these results, it is advised that healthcare professionals integrate comparable educational initiatives into standard maternal and infant care practices.